A study on the effect of different farm manures on the early growth of corn - Baylon, Mario Luis Escalante
A study on the influence of four farm manures namely, bat, hog, carabao and chicken manures, on the early growth of corn was conducted. It was observed that bat manure (guano) gave the tallest height and greatest mean number of leaves on the corn plant, followed by chicken dung, then carabao manure and lastly, hog manure. The difference in the mean height of corn under treatments with the four manures statistically significant over the control which consisted of garden soil-sand mixture alone. Root and leaf development were also more pronounced among the treatments with farm manures as compared to the control.